Computer-Assisted Surgical Anatomical Mapping of the Antebrachial Cutaneous Nerves - Lisette C. Langenberg, MD; Alexander R. Poublon, MD, PhD; Lieke Hofman, BSc; Gert-Jan Kleinrensink, MSc, PhD; Denise Eygendaal, MD, PhD (JBJS Open Access, 2023)
Background:. It is common practice to assess the distance from nerves to anatomical structures in centimeters, but patients have various body compositions and anatomical variations are common. The purpose of this study was therefore to assess the relative distance from cutaneous nerves around the elbow to surrounding anatomical landmarks by providing a stacked image that displays the average position of cutaneous nerves around the elbow. The aim was to research possibilities for adjusting common skin incisions in the anterior elbow so that cutaneous nerve injury may be avoided. Methods:. The lateral antebrachial cutaneous nerve (LABCN) and medial antebrachial cutaneous nerve (MABCN) were identified in the coronal plane around the elbow joint in 10 fresh-frozen human arm specimens. Marked photographs of the specimens were analyzed using computer-assisted surgical anatomical mapping (CASAM). Common anterior surgical approaches to the elbow joint and the distal humerus were then compared with merged images, and nerve-sparing alternatives are proposed. Results:. The arm was divided longitudinally, from medial to lateral in the coronal plane, into 4 quarters. The LABCN crossed the central-lateral quarter of the interepicondylar line (i.e., was somewhat lateral to the midline at the level of the elbow crease) in 9 of 10 specimens. The MABCN ran medial to the basilic vein and crossed the most medial quarter of the interepicondylar line. Thus, 2 of the quarters were either free of cutaneous nerves (the most lateral quarter) or contained a distal cutaneous branch in only 1 of 10 specimens (the central-medial quarter). Conclusions:. The Boyd-Anderson approach, which is often used to access anteromedial structures of the elbow, should be placed slightly further medially than traditionally advised. The distal part of the Henry approach should deviate laterally, so that it runs over the mobile wad. In distal biceps tendon surgery, the risk of cutaneous nerve injury may be reduced if a single distal incision is placed slightly more laterally (in the most lateral quarter), as in the modified Henry approach. If proximal extension is required, LABCN injury may be prevented by using the modified Boyd-Anderson incision, which runs in the central-medial quarter. Clinical Relevance:. Cutaneous nerve injury may be prevented by slightly altering the commonly used skin incisions around the elbow on the basis of the safe zones that were identified by depicting the cumulative course of the MABCN and LABCN using CASAM.